PENGARUH METODE MAKE A MATCH TERHADAP KECERDASAN EMOSIONAL ANAK USIA 5-6 TAHUN DI TK ISLAM FATIMAH KECAMATAN TAMPAN PEKANBARU - Heni Sumanti; Daviq Chairilsyah; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to determine whether there are significant implementation problems methods make a match in children aged 5-6 years at Islam Fatimah kindergarten District of Pekanbaru. The research method is observation using observation sheet. Sample of this research are 22 children of class. The data collection techniques were used that observation and documentation. Data were analyzed using t-test using SPSS 17.0. The study hypothesis is make a match method has an effect on emotional intelligence aged 5-6 years at Islam Fatimah kindergarten Tampan District of Pekanbaru. This is knowing from the result of data obtained t = 19.271 and Sig. (2-tailed) = 0,000. because p < 0,05. So, It can be interpreted that there is a difference in the success rate of emotional intelligence of children before and after treatment using methods make a match. So, it’s mean that Ho refused and Ha accepted that means there are very significant different between before and after doing the performing experiments by applying a make a match. Effect of methods make a match of the emotional intelligence of children aged 5-6 years at Islam Fatimah kindergarten Tampan District of Pekanbaru of 40, 6%. the middle category.